Representation Women in Movie "Telur Setengah Matang" (Roland Barthes Semiotic Snalysis) - Adhilistyo, Dimas Fajar; Apriliani, Riski (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to describe the representation of women in the short film Telur Setengah Matang by director Reni Apriliani. This research uses a descriptive qualitative approach. The research method uses Roland Barthes' Semiotic Analysis with two-way significance and the meaning of denotation, connotation and myth. The subject of this research is Nisa, the object of this research is women who are represented in scenes, dialogue and characters in films. Data collection methods include observation, literature study, interviews and documentation. The short film Telur Setengah Matang tells the story of how Nisa, a teenager, has to take responsibility for consequences they didn't think about before because of premarital sex. This film also illustrates the important role of parents in communicating information about sex to children. The results of this research show that there is a depiction of sex education in films. The side or form of sex education is shown in scene excerpts, dialogue, or characters that emphasize the importance of knowing sex education and knowing the consequences of every action related to sex.